Sustaining and accelerating Africa's agricultural growth recovery in the context of changing global food prices - Badiane, Ousmane (International Food Policy Research Institute, 2008)
Starting in the mid-1990s, Africa embarked upon its longest period of sustained, positive per capita income growth since the 1960s. This growth recovery has made a dent in poverty and holds out hope that a number of African countries may reach the Millennium Development Goal targets for poverty and food security (MDG 1), if not by 2015, then within the following few years. Agricultural growth has been, and will remain, key to reducing poverty and hunger in Africa. To significantly reduce poverty, Africa needs to sustain, broaden, and accelerate its recent growth performance and boost its investments in agriculture. The recent spike in global food prices represents an opportunity that could support further agricultural sector growth in Africa. The unfolding financial crisis, on the other hand, could have the reverse effect, especially if it leads to lower investments in the sector.